48 Use of amiodarone for direct current cardioversion – a five year study. (28th September 2016) - Sharif, Z; Yogeswaren, S; Ahmad, S; Cosgrave, J
Abstract : Background: Despite sub-optimal long-term results DC electrical cardioversion (DCCV) remains a main stay in atrial fibrillation (AF) management. In selected patients long-term success at 6 weeks is approximately 50%. Amiodarone has been shown to be effective in maintaining normal sinus rhythm (NSR), as demonstrated in the AF-CHF trial, in which NSR in the rhythm control arm after 5 years was approximately 80%. Methods: We aimed to assess amiodarone efficacy in maintaining NSR post DCCV at our centre from January 2008 to December 2013. Through retrospective chart analysis we identified patients undergoing first DCCV within this time period. Patients were followed up at 6 weeks and 6 months. Medication changes and rhythm status were documented. Baseline characteristics, medications and length in AF pre-DCCV were documented. Safety profile was determined. Results: 152 patients underwent DCCV within this time period; 129 on amiodarone, 5 on alternative anti-arrhythmic, and 18 off anti-arrhythmic. 7.89% patients had a history of MI, 15.13% a history of PCI and 5.28% had a history of CABG. Average AF duration was 15.5 months. 19.7% and 7.2% of patients had moderate and severe left ventricular dysfunction respectively. At 6 weeks 64.4% patients on amiodarone were in NSR versus 33.3% not receiving such (p = 0.023). At 6 months 51% patients on amiodarone were in NSR versus 16.67% not receiving such (p = 0.081). 7 patients suffered thyroid dysfunction, and 4 patients suffered LFT derangement. Conclusion: In an unselected high risk population the addition of amiodarone suggests improved long-term outcomes, with good drug tolerance. This data suggests a larger randomised control trial of amiodarone-facilitated DCCV may be warranted.